Core level spectroscopy of solids - Groot, Frank de, 1964-; Kotani, A. (Akio), 1941- (Boca Raton : CRC Press, 2008)
"From fundamental aspects to recent developments. Core Level Spectroscopy of Solids presents the theoretical calculations, experimental data, and underlying physics of core level spectroscopies. This includes x-ray photoemission spectroscopy (XPS), x-ray absorption spectroscopy (XAS), x-ray magnetic circular dichroism (XMCD) and resonant x-ray emission spectroscopy (RXES). The book explains the many-body effects in XPS and XAS, where special attention is given to charge transfer, crystal field, and multiplet effects, Charge transfer multiplet theory combines these effects into a single theoretical approach that can be used to interpret XPS, XAS, and all other core level spectroscopies of systems, including transition metal and rare earth elements."--BOOK JACKET.
Ch. 1. Introduction -- Ch. 2. Fundamental Aspects of Core Level Spectroscopies -- Ch. 3. Many-Body Charge-Transfer Effects in XPS and XAS -- Ch. 4. Charge Transfer Multiplet Theory -- Ch. 5. X-Ray Photoemission Spectroscopy -- Ch. 6. X-Ray Absorption Spectroscopy -- Ch. 7. X-Ray Magnetic Circular Dichroism -- Ch. 8. Resonant X-Ray Emission Spectroscopy -- App. A. Precise Derivation of XPS Formula -- App. B. Derivation of Equation 3.88 in Chapter 3 -- App. C. Fundamental Tensor Theory -- App. D. Derivation of the Orbital Moment Sum Rule -- App. E. Theoretical Test of the Spin Sum Rule -- App. F. Calculations of XAS Spectra with Single Electron Excitation Models.
Includes bibliographical references (p. 463-481) and index.
Keywords: Solids -- Spectra; Spectrum analysis; Electron spectroscopy; Energy-band theory of solids